Proof-of-concept of duplex MNAzyme assay for simultaneous detection of Candida auris and Candida spp. using synthetic DNA targets - Jainlabdin, Mohd Hanif; Ahmed Al-Shaibani, Muhanna Mohammed; Abdel Wahhab, Mosaad Attia; Mohd Ali, Mohammad Ridhuan; Edwards, Thomas; Tovar-Torres, Jorge (Malaysian Society for Molecular Biology and Biotechnology (MSMBB), 2025)
The global emergence of Candida auris as a multidrug-resistant fungal pathogen presents significant challenges to healthcare systems, particularly in hospital settings. Rapid and accurate diagnostics are crucial for managing C. auris infections. This study presents a preliminary analytical evaluation of a duplex Multicomponent Nucleic Acid Enzyme (MNAzyme) assay designed to simultaneously detect C. auris and genus-wide Candida species using synthetic DNA targets. Target sequences were selected from the conserved D1/D2 region of the LSU rDNA locus, and melting temperature analysis confirmed distinct probe hybridisation profiles, with Substrate 2:PCO1 yielding a Tm of 45°C and Substrate 3:PCO4 at 26°C. The assay demonstrated specificity by differentiating C. auris from other Candida species through melting curve analysis. In reactions containing synthetic targets, probe– target binding disrupted probe–PCO hybrids, resulting in a marked reduction in melt peaks compared to no DNA controls (NDC). The duplex format allows multiplex detection within a single fluorescence channel, offering a potential advantage over conventional single-target assays. This proof-of-concept establishes a rapid, low-cost diagnostic platform with promising potential for future clinical application. Further validation using clinical and environmental samples is needed to support its broader utility in detecting fungal pathogens.